Identifying environmental risk to male reproductive function by occupational sperm studies: logistics and design options. - Bonde, J P (1996)
Malfunction of the male reproductive system might be a sensitive marker of environmental hazards, the effects of which may extend beyond reproductive function. The testis is more vulnerable to heat and ionising radiation than any other organ of the body and several xenobiotics are known to disrupt spermatogenesis after low level exposure. Studies of environmental impact on human health are often most informative and accurate when carried out in the workplace where exposures can be high and easy to document. Semen analysis provides readily obtainable information on testicular function. The main advantages in comparison with functional measures such as fertility rates and time taken to conceive are the possibilities to examine men independently of marriage and pregnancy, to find changes of fecundity with different exposures within the same person and to detect adverse effects when no alteration of fertility is yet taking place. In the implementation of an occupational sperm study considerable attention must be paid to logistic issues. A mobile laboratory unit for initial semen preparation and processing may in some situations increase worker compliance and the quality of sperm cell motility. The cross sectional design which has been used in almost all male reproductive studies so far has several severe limitations including selection bias because of differential participation, difficulties in defining a suitable reference group, and lack of information about the time dimension of the cause-effect relation. The longitudinal design deals adequately with most of these constraints. Semen samples are collected before, during, and possibly after exposure to the risk factor of interest and causal inferences are based upon change of semen variables within a man over time rather than upon differences between men. The logistics of the longitudinal study may benefit from pre-employment health examinations to enrol newly hired workers and require fewer participants to obtain comparable statistical power. In conclusion, andrological methods and epidemiological designs are available for the implementation of valid studies concerned with environmental impact on human testicular function. Occupational sperm studies should probably not be the first choice when the objective is initial screening of environmental impact on fertility but should be implemented when their is a need to corroborate or refuse earlier evidence that specific exposures have impact on testicular function.